Modern presentation of the content of the activities of the construction and engineering firm - Tugai А.; Orischenko, V. (Ways to Improve Construction Efficiency, 2019)
Formally-analytical and organizational bases of positioning of building-engineering firms are expounded at the building market. Advantages of change of functions of the indicated firms are well-proven in an investment process - from functions exceptionally engineering to new quality - general contractor of new type responsible to the investor for the intermediate and final results of introduction of building project.